Chia and flaxseed flours fermented by lactic acid bacteria for the production of gluten free baked products - Dentice Maidana, Stefania (2018)
Chia and flaxseed flours are widely consumed due to their health and nutritional benefits as high proteins and omega-3 content and gluten free properties. Fermentation of these high-protein flours (sourdoughs) is characterized by a complex microbial ecosystem, mainly represented by lactic acid bacteria (LAB) and yeasts, the resulting products exhibiting high palatability and sensory quality. Selected LAB (Weisella (W.) cibaria C-2, Lactobacillus (Lb.) plantarum FUA3161 and Lb. fermentum FUA3171) were used as functional cultures. Microbiological and technological features (peroxidase and proteolytic activities, water-soluble polysaccharides hydrolysis and organic acids production) of the strains in flour slurries were evaluated and sensory analysis of final fermented products (by an untrained panel) were carried out. W. cibaria C-2 was able to produce higher hydrogen peroxide concentration during sourdough fermentation than those obtained with Lb. plantarum FUA3161 or Lb. fermentum FUA3171. Among analyzed strains, moderate protein degradation and soluble polysaccharides hydrolysis were produced by W. cibaria C-2 showing accumulation of xylose > arabinose >> rhamnose and organic acids production (lactate >> ethanol > acetate). Then, LAB strains (107 UFC/g) were used as inoculum (individually and in combination) for sourdoughs production (chia and flaxseed). To obtain a baked product, different proportions (5, 10, 20, 30 y 40 %) of the pre-ferment was added to a mixture (sorghum flour, xanthan gum, sucrose, NaCl and yeast), incubated at 30 ºC for 90 min and cooked in an oven at 350 ºC, 35 min. Low percentages of pre-ferments had higher incidence in products specific volume. When sensory evaluation was performed, it was able to distinguish (> 50% of panelists) baked products inoculated with W. cibaria C-2 as those with higher taste, texture and overall aspect. The data show the great potential of LAB as alternative for improving sourdough (chia and flaxseed) fermentation.